2021
DOI: 10.3390/v13020284
|View full text |Cite
|
Sign up to set email alerts
|

Titers of Neutralizing Antibodies against SARS-CoV-2 Are Independent of Symptoms of Non-Severe COVID-19 in Young Adults

Abstract: Neutralizing antibodies are an important part of the humoral immune response to SARS-CoV-2. It is currently unclear to what extent such antibodies are produced after non-severe disease or asymptomatic infection. We studied a cluster of SARS-CoV-2 infections among a homogeneous population of 332 predominantly male Swiss soldiers and determined the neutralizing antibody response with a serum neutralization assay using a recombinant SARS-CoV-2-GFP. All patients with non-severe COVID-19 showed a swift humoral resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…Lower antibody levels in nurses and physicians than other HCW could indicate a lower exposure due to PPE use and higher awareness of risks [19]. Smoking had previously been associated with lower antibody responses [22,23] and we show that this effect persists after several months primarily affecting IgA, the main mucosal antibody.…”
Section: Resultssupporting
confidence: 45%
“…Lower antibody levels in nurses and physicians than other HCW could indicate a lower exposure due to PPE use and higher awareness of risks [19]. Smoking had previously been associated with lower antibody responses [22,23] and we show that this effect persists after several months primarily affecting IgA, the main mucosal antibody.…”
Section: Resultssupporting
confidence: 45%
“…Recent population-based studies during the pandemic showed that smoking is a major factor associated with lower response to the SARS-CoV-2 vaccine [ 45 ]. Other recent studies showed that smokers had lower antibody titers, suggesting an impaired humoral response [ 46 , 47 , 48 ]. Our results contribute to the above evidence and show that smoking is a significant negative factor for impaired humoral immunity in vaccinated cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using such an algorithm, we found that 39.3%, 38.1% and 32.2% of the tested participants had anti-N IgM ± IgG, anti-S1 IgM ± IgG and nAbs, respectively. While this might indicate that not all individuals with nAbs in this study produced IgM and/or IgG against N and S1 proteins, one cannot ignore the fact that some might have no or low antibody responses [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%